Enhancing effect of nitrogen on grain production of hybrid maize in Chitwan valley - Adhikary, BH; Adhikary, R (Agronomy Journal of Nepal, 2013)
Nitrogen is one of the key factors for increased grain production of hybrid maize. A newly developed hybrid maize variety Rampur Hybrid-2 was evaluated for grain production by the application of different levels of nitrogen (60, 120 and 180 kg N/ha) at varying plant densities (55555, 66666 and 83383 plants/ha) along with 60 kg P2O5 and 40 kg K2O /ha in the acidic soil (pH 5.3) of National Maize Research Program, Rampur, Chitwan during the years of 2008/09 and 2009/10. Factorial randomized complete block design (RCBD) with three replications was the design of experiment. The crop was planted at the plot size of 18 m2 (3.6 m × 5 m). maize was planted in the month of September and harvested in February. The result indicated a sharp response of nitrogen application to this crop whereas the effect of density was observed to be non-significant. Two years mean yield results showed that highest grain yield (11.10 t /ha) was recorded when the crop was supplied with 180 kg nitrogen and with 83383 plants /ha followed by the crop supplied with 120 kg N /ha and 66,666 plant population (10.69 t /ha). The experimental results revealed that application of high dose of N (180 kg N /ha) could help increase hybrid maize grain production in the acidic soils of Chitwan valley. Agronomy Journal of Nepal (Agron JN) Vol. 3. 2013, Page 33-41 DOI: http://dx.doi.org/10.3126/ajn.v3i0.8984